Analisis Kemampuan Numerasi Siswa Dalam Menyelesaikan Soal Pola Bilangan - Darmono, Prasetyo Budi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The aim of this study was to describe the numeracy ability of the students in solving class IX junior number pattern questions. This type of research is qualitative research with a phenomenological approach. The subjects of this study were selected based on the students’ mathematical ability i.e. it consists of 6 subjects with each 2 students for each mathematical ability (high, medium, and low) Grade IX Bhakti Karya Karya Gebang Junior High School. The technique used in the sampling of subjects was purposive sampling. Research instruments take the form of a main instrument (researcher) and a supporting instrument (number pattern test). The research data collection techniques used tests, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and inference drawing. The results of the study showed that the numeracy ability of students with high mathematics ability was able to meet 3 indicators of numeracy ability, numeracy ability of students with moderate mathematics ability was able to meet 2 indicators of numeracy ability, and numeracy ability of mathematics ability only1 indicator of low ability numbering.